Students’ interest in using robo-advisors: The role of financial knowledge and online behavior - Nguyen , Minh Hải (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
This study surveys the interest of students from the Faculty of Economics at Binh Duong University in using robo-advisory services and analyzes the role of financial knowledge and online behavior in shaping this interest. The results show that students with advanced financial knowledge are particularly interested in using robo-advisors. Finance and Banking students demonstrate a higher level of interest compared to those from the Accounting and Business Administration majors. Additionally, only online behaviors related to financial activities, such as online shopping and digital payments, can predict interest in robo-advisors. In contrast, non-financial online activities do not influence students’ interest in this tool